(3aUd aj EbGeI CQcGf GdUdGI hGdWeCfjfI ajgGs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3GdMeO ddg aUd ai HjGf eG CeQ Gddg Hg hQShdg ef EbGeI GdUdGI HEJeGegG hGdWeCfjfI ajgG bGd Gddg JYGdi (B" (3hCbjehG GdUdGI hBJhG GdRcGI (B) (3ai ZjQ ehVY ef cJGHg s
(3BNQgG (B:s
(3hge CNPhG GdYde Yf YHO Gddg hfMhg abO JHjf Cf GdCeQ djS cPdc hGddg SHMGfg hJYGdi CYde HGdUhGH hUdi Gddg Ydi SjOfG eMeO hidg hUMHg hSde Je GdLhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG eWGdH ddcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfHdjs